Aleitamento materno e hábitos de sucção no primeiro ano de vida - Pinheiro, Suélem Maria Santana (2012)
Breastfeeding is a unique practice in childhood, to reach nutritional and emotional satiety. The latter, at the oral phase, is subject to the mouth, considered as the first erotogenic area of the child control. Thus, when the practice of breastfeeding does not occur in a satisfactory manner, the child uses other mechanisms to satisfy their urge to suck, started developing sucking habits. Rationale: The impact of these habits on the stomatognathic system culminates in the installation of morpho-functional alterations, on chewing, swallowing, phonation and breathing, contributing to abnormalities in facial growth, positioning and development of dental malocclusion. So it is valid to show their conditioning factors for action on them. Objective: To estimate the association between exclusive breastfeeding until 4 and 6 months, and pacifier sucking habit at 12 months. Method: This study is part of a cohort of newborns in the city of Feira de Santana, Bahia, Brazil, and used data from 1037 children followed until 12 months of life. Data collection proceeded with built form in 4 steps, applied according to the child's age. The sample was divided into four groups, according to food investigation, with 24-hour recall: Group with exclusive breastfeeding, predominant breastfeeding Group, Group with complementary breastfeeding and no breastfeeding group. In addition, children were classified according to presence or absence of pacifier sucking habit. The results were analyzed descriptively. Subsequently, the Chi-square test, relative risk and confidence interval were used to measure differences between groups. And finally, stratified analysis and multivariate analyzes were used for potential treatment of modifiers and confounders co-variables. Results: The results are presented in the form of a scientific paper entitled "Exclusive breastfeeding and pacifier sucking habits in children - a cohort study." They showed that the risk of pacifier sucking habit at 12 months of age was higher in children on complementary breastfeeding (1.68 times and 1.43 times) and those without breastfeeding (2.67 times and 3.30 times), both up to 4 and 6 months, respectively, when compared to those infants under exclusive breastfeeding. These results, statistically significant, were obtained after adjustment for maternal color, number of pre-natal consultations, and family income. Conclusion: The non-realization of breastfeeding was a risk factor for pacifier sucking habit, in contrast to exclusive breastfeeding, which exerted a protective role against the sucking habit.